(untitled) (Marketing Journal, 2025)
This article analyzes the importance of utilitarian value as a key factor influencing consumer purchasing decisions in the Uzbek smartphone market. The qualitative 15 approach was chosen as the meth odological basis for the study, and local and foreign scientific sources, statistics, and analytical reports published in 2017 –2025 were studied using the content analysis method. The main attention was paid to the functional criteria of consumers in choos ing products — battery life, technical capabilities, service quality, and price –quality ratio. Based on the analysis, it was determined that the high market share of brands such as Samsung and Xiaomi is associated with products that meet utilitarian values , and practical suggestions were made to take this factor into account when developing competitive marketing strategies.